Etnolinguistik Dhukun Pijet di Kabupaten Semarang: Menggali Makna dan Kearifan Lokal - Febri Magit Setyoko; Suwardi Endraswara; Doni Dwi Hartanto (Jurnal Bahasa dan Sastra, 2026)
This study examines linguistic unitsi dhukun pijet activities performed by traditional healers in Candirejo Village, Semarang Regency Semarang. This study aims to reveal the lexical and cultural meanings, as well as the local wisdom contained in the linguistic units of traditional massage therapy. This study uses a qualitative descriptive approach, with data collected through participant observation, in-depth interviews, and documentation, then validated using triangulation of techniques and sources. The results of the study identified 51 linguistic units classified into categories of words and discourse. Word linguistic units were categorised based on the names of diseases (20), massage tools (11), massage techniques (9), and body parts (8). Discourse linguistic units were based on massage healers' incantations (3). Analysis showed there was a referential function, with linguistic units containing cultural meaning. The local wisdom that emerged was classified into three categories: knowledge, taboos, and mystical spirituality. This study concludes that the linguistic units that emerge in the traditional massage practitioner's healing process are not only technical communication tools but also linguistic scientific documentation within Javanese culture, thereby serving as a learning reference for futuregenerations. Key words: dhukun pijet; Lingual Unit; Meaning; local Wisdom; Eethnolinguistic